43.5k views
3 votes
Solve for z.

ln63=lnz+ln7

Enter your answer in the box.

2 Answers

5 votes

Answer:

ln(56 + -1z) = 0

Explanation:

Simplifying

ln(63) = ln(z) + ln(7)

Reorder the terms for easier multiplication:

63ln = ln(z) + ln(7)

Multiply ln * z

63ln = lnz + ln(7)

Reorder the terms for easier multiplication:

63ln = lnz + 7ln

Reorder the terms:

63ln = 7ln + lnz

Solving

63ln = 7ln + lnz

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-7ln' to each side of the equation.

63ln + -7ln = 7ln + -7ln + lnz

Combine like terms: 63ln + -7ln = 56ln

56ln = 7ln + -7ln + lnz

Combine like terms: 7ln + -7ln = 0

56ln = 0 + lnz

56ln = lnz

Add '-1lnz' to each side of the equation.

56ln + -1lnz = lnz + -1lnz

Combine like terms: lnz + -1lnz = 0

56ln + -1lnz = 0

Factor out the Greatest Common Factor (GCF), 'ln'.

ln(56 + -1z) = 0



Could be wrong. If it is, let me know. Thanks! Have a good rest of your day! :)

User Kfaerber
by
4.9k points
7 votes

Answer:

z = 9

Explanation:

ln 63 = ln z + ln 7

We have the formula:

ln A + ln B = ln AB

So, ln 63 = ln 7z

7z = 63

Divide both sides by 7.


(7z)/(7)=(63)/(7)

z = 9

User SomethingSomething
by
5.7k points